Disfavoring the Schrödinger-Newton equation in explaining the emergence of classicality - Da Silva, João V. B. [UNESP]; Aguiar, Gabriel H. S. [UNESP]; Matsas, George E. A. [UNESP] (American Physical Society (APS), 2023)
The main goal of this paper is to provide some insight into how promising the Schrödinger-Newton equation would be to explain the emergence of classicality. Based on the similarity of the Newton and Coulomb potentials, we add an electric self-interacting term to the Schrödinger-Newton equation for the hydrogen atom. Our results rule out the possibility that single electrons self-interact through their electromagnetic field. Next, we use the hydrogen atom to get insight into the intrinsic difficulty of testing the Schrödinger-Newton equation itself and conclude that the Planck scale must be approached before sound constraints are established. Although our results cannot be used to rule out the Schrödinger-Newton equation at all, they might be seen as disfavoring it if we base our reasoning on the resemblance between the gravitational and electromagnetic interactions at low energies.